KARAKTERISTIK VULKANISASI KOMPON PADA PEMBUATAN WIPER BLADE - Prasetya, Hari Adi; Marlina, Popy (Jurnal Dinamika Penelitian Industri, 2010)
The research aimed to study the effect of temperature and Hydrocxilamin Netral Sulphat (HNS)Â  to characteristics of vulcanization wiper blade. Temperature vulcanization used for the research was varied at 130 oC, 150 oC, 170 oC and Hydrocxilamin Netral Sulphat (HNS) at 5 phr, 10 phr. The result show that the effect temperature of vulcanization and Hydrocxilamin Netral Sulphat (HNS) consentration had significant effect on the scorch time (ts2), optimum cure time (t90), vulcanization rate, and modulus torsi (t) rubber compound wiper blade. The best treatment was found to be the T2H2(the addition of temperature 150 oC and HNS 10 phr) with characteristic of vulcanization wiper blade compound of 2,25 minute for the scorch time, 4 minute for the optimum cure time, 12, 12 minute for the vulcanization rate and 82kg.cm for the torcy modulus.